2015
DOI: 10.4103/2347-9264.157108
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the flexor carpi radialis tendon secondary to trauma: case report and literature review

Abstract: The flexor carpi radialis (FCR) is one of the long flexors, which is important in flexing and abducting the hand at the wrist. It originates at the medial epicondyle of the humerus and attaches at the base of the second metacarpal. Closed rupture of the long flexors of the finger is well-described, especially in association with rheumatoid hands. However, rupture of the FCR is rare; only 11 cases reported in the literature, most of them associated with scaphotrapezial-trapezoidal osteoarthritis. We describe 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“… 4 Although FCR injuries in athletes are rare, they have been previously described. 5 However, even with direct trauma to the muscle or myotendinous junction, tendinitis or rupture still manifests distally within the fibro-osseous tunnel. 5 We hypothesize that our patient had an acute partial tear of the proximal FCR tendon during the single symptomatic javelin throw that she recalled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Although FCR injuries in athletes are rare, they have been previously described. 5 However, even with direct trauma to the muscle or myotendinous junction, tendinitis or rupture still manifests distally within the fibro-osseous tunnel. 5 We hypothesize that our patient had an acute partial tear of the proximal FCR tendon during the single symptomatic javelin throw that she recalled.…”
Section: Discussionmentioning
confidence: 99%
“… 5 However, even with direct trauma to the muscle or myotendinous junction, tendinitis or rupture still manifests distally within the fibro-osseous tunnel. 5 We hypothesize that our patient had an acute partial tear of the proximal FCR tendon during the single symptomatic javelin throw that she recalled. Over time, continued throwing likely resulted in chronic tendinitis, calcification, and scarring to the overlying skin at the myotendinous junction.…”
Section: Discussionmentioning
confidence: 99%
“…The study also validated that when a lead arm straight punch is thrown on the head, there is a quarter turn of the torso and pelvis, which adds additional torque to the upper body movement and due to which peak muscular activity might be observed for the deltoid and biceps muscle group. It is observed that FCR begins at the medial epicondyle of the humerus and connects to the second metacarpal at the base, and it is crucial for flexing and abducting the hand at the wrist (Kanevsky et al, 2015), whereas the flexion of the wrist is an involuntary movement during impact on the target area in boxing, so highest peak activation for FCR muscle might be due to more flexion at the wrist joint during the execution of jab in MRB technique. The TB muscle is responsible for the extension of the elbow at shoulder elevation and contributes more to elbow extension (Kholinne et al, 2018), while UT is also responsible for elevation and depression of the shoulder (Shih & Kao, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…특히 요수근 굴곡건(flexor carpi radialis tendon)의 폐쇄성 파열은 류마티스 관절염 환자가 아 닌 경우 드물게 발생한다고 알려져 있다 [2]. 류마티스 관절염 이외, 손목의 골절 및 기 타 외상, 스테로이드 주사 후 혹은 수근골 관절염에 의한 마멸성 파열이 발생할 수 있 으나 [1][2][3]…”
Section: 서론unclassified